The Effect of Solar Panel Output Power Analysis with Reflector Angle Optimization and Addition of Heatsink-Fan Cooling System - Suryo, Taufik Hadi; Rhakasywi, Damora; Fahrudin, Fahrudin (Journal of Applied Science, Engineering, Technology, and Education, 2023)
The addition of reflectors to solar panels is used to increase the intensity of sunlight received by solar panels so that the electrical power generated by the panels increases. In adding reflectors to solar panels, they must consider various factors to be able to increase the power generated without having a negative effect on solar panels , one of which is providing a cooling system. Therefore, research is needed to increase the power generated by solar panels and cooling systems that are suitable for overcoming rising temperatures due to the addition of reflectors. The study was conducted by varying the glass mirror reflector, aluminum foil reflector, angle of the reflector, and heatsink-fan cooling system. The research method used in this study was to compare 2 solar panel models, namely: solar panels with the addition of glass mirror reflectors / aluminum foil and heatsink-fan cooling systems, and solar panel models without any addition. The results show that the solar panel model with the addition of a glass mirror reflector / aluminum foil can increase the output power according to the angle of the reflector, the highest increase reaching 16.70% in the 450-angled aluminum foil mirror reflector. The heatsink cooling system is considered to be useful for reducing the temperature of solar panels, but the decrease is relatively small below 5%.